A Farming System Approach to Exploring Drivers of Food Insecurity Among Farm Households in Developing Countries: The Case Study of Mozambique - Máriam Abbas; Paulo Flores Ribeiro; José Lima Santos (Agronomy)
Farm households, especially in developing countries, are among the most vulnerable to food insecurity and poverty. A farming system approach is largely recognized to play an important role in supporting strategies to improve food security and alleviate poverty among farm households. This paper aims at exploring the drivers of food insecurity among farm households in developing countries, using a farming system approach. It also aims to explore farm households’ perceptions regarding the causes of food shortages and the adopted coping strategies, and how these vary across farming systems. This analysis was based on data extracted from an agricultural census, which were analyzed through scatter plots and plot means with 95% confidence intervals. The results indicate that the factors analyzed (level of specialization, market integration, use of yield-raising and labor-saving inputs, farm size, population density, and rainfall) are important drivers explaining food insecurity among farm households, highlighting important differences across farming systems. The analysis also showed that farm households’ perceptions regarding the causes of food shortages are related with the abovementioned drivers of food insecurity. Our findings suggest that less specialized farming systems with better access to markets, using yield-raising and/or labor-saving inputs, are more likely to be food secure. The farming system approach proved to be a useful approach to explore food insecurity drivers and coping strategies as well as to support policymaking. Moreover, the use of an agricultural census data provides an easily attainable tool to access and analyze farm-level data for policy analysis and to explore and understand a range of issues affecting farm households in developing countries.